2016
DOI: 10.1248/bpb.b16-00411
|View full text |Cite
|
Sign up to set email alerts
|

7-(4-Hydroxyphenyl)-1-phenyl-4<i>E</i>-hepten-3-one, a Diarylheptanoid from <i>Alpinia officinarum</i>, Protects Neurons against Amyloid-β Induced Toxicity

Abstract: Amyloid-β (Aβ) is one of the major causative agents of Alzheimer's disease (AD), the most common neurodegenerative disorder characterized by progressive cognitive impairment. While effective drugs for AD are currently limited, identifying anti-Aβ compounds from natural products has been shown as a promising strategy which may lead to breakthroughs for new drug candidate discovery. We have previously reported that 7-(4-hydroxyphenyl)-1-phenyl-4E-hepten-3-one (AO-1), a diarylheptanoid extracted from the plant Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…They also notably protected hippocampal HT22 cells from glutamate insult-induced neurotoxicity. Overall, diarylheptanoids may mitigate memory deficiency by activating the BDNF–CREB pathway and inhibit neuronal cell death to prevent neurodegeneration [ 43 , 44 ]. Besides, leaves of B. pinnatum and bark of G. pinnata were reported to present potent anti-inflammatory nonsteroidal derivatives [ 10 ], phytosterols, triterpenoids, alkaloids, glycosides, polyphenol, β -amyrin structure, and so on [ 34 , 35 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also notably protected hippocampal HT22 cells from glutamate insult-induced neurotoxicity. Overall, diarylheptanoids may mitigate memory deficiency by activating the BDNF–CREB pathway and inhibit neuronal cell death to prevent neurodegeneration [ 43 , 44 ]. Besides, leaves of B. pinnatum and bark of G. pinnata were reported to present potent anti-inflammatory nonsteroidal derivatives [ 10 ], phytosterols, triterpenoids, alkaloids, glycosides, polyphenol, β -amyrin structure, and so on [ 34 , 35 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that AO‐2 reduces the levels of phosphor‐p38 MAPK, a signalling molecule that leads to inflammatory responses . Indeed, accumulating evidence indicates diarylheptanoids has anti‐inflammatory roles . It would be thus of interest to examine whether AO‐2 also inhibits OGD‐induced neuroinflammation in glial cells such as microglia.…”
Section: Discussionmentioning
confidence: 99%
“…2). Huang et al (2016) showed that the compound 7-(4-hydroxyphenyl)-1-phenyl-4E-hepten-3-one, a diarylheptanoid extracted from 95% ethanolic extract of A. officinarum rhizome, presents effects on neuronal differentiation and neurite outgrowth in vitro. 7-(4-hydroxyphenyl)-1-phenyl-4E-hepten-3-one (0.5-10 μM) had neuroprotective effects against the neurotoxicity caused by Aβ, attenuated the damage of Aβ oligomers, and reduced apoptotic levels and oxidative stress triggered by Aβ.…”
Section: Alpinia Officinarum Hancementioning
confidence: 99%